Growth performances of Clarias gariepinus juveniles fed with Jatropha curcas seed meal - Jeremiah Olanipekun Jimoh; Sharifah Rahmah; Bamidele Oluwarotimi Omitoyin; Emmanuel Kolawole Ajani; Mohamad Jalilah; Victor Tosin Okomoda; Donald Torsabo; Abiola Ayodeji Fabusoro; Yu Mei Chang; Young-Mao Chen; Hon Jung Liew (Aquaculture Reports)
Jatropha curcas is an oil producing seed with high nutritional qualities for consumption. However, due to inherent anti-nutritional factors, appropriate processing is necessary to improve its nutrients utilization. This study was aimed at processing J. curcas using solvent-extraction method and evaluating its inclusion effects in the diet for Clarias gariepinus on its growth status. J. curcas meal was extracted using 80 % methanol to remove phorbol esters and other anti-nutrients. Thereafter, five iso-nitrogenous diets (40 % crude protein) were formulated containing J. curcas meal replacements of soybeans meal at 0 % (TRT0), 25 % (TRT25), 50 % (TRT50), 75 % (TRT75) and 100 % (TRT100) and fed to C. gariepinus for 70 days. Results showed that TRT25 fish had the highest mean weight gain and specific growth. The serum alkaline phosphate, alanine aminotransferase, and aspartate aminotransferase levels began to rise significantly (p ≤ 0.05) at 50 % replacement. Likewise, the assessment of gut ecology and morphology indicated that TRT25 had significantly (p ≤ 0.05) the highest gut bacteria colony forming unit (2.60 ×104±0.02cfu/g) and most favorable area of absorption (0.16±0.01 cm2). The histopathological observation of the fish intestine, liver and gills indicated no visible deformity in TRT0 and TRT25 fish. However, various degrees of degenerations were observed in the fish fed with 50 % and higher inclusion of J. curcas. This study showed that methanol-extracted J. curcas meal can be effectively utilized for C. gariepinus at 25 % of replacement.